Callus Culture of Arceuthobium americanum Nutt. ex Englem. and Explant Response to Varying Auxin and Cytokinin Concentrations - Martin, Lyssa L.; Friedman, Cynthia Ross; Smith, Ronald G. (Plant Tissue Culture and Biotechnology, 2012)
The lodgepole pine dwarf mistletoe Arceuthobium americanum is a severe pest in coniferous forests of western North America. To facilitate laboratory studies of this obligate parasite, a modified White’s medium was used for in vitro culture; the concentrations of IAA and Kn were varied to determine optimal IAA/Kn ratios. It was found that explant health was related to the concentration of IAA (p = 0.008), but not Kn (p = 0.937), and that explants were healthiest at an IAA/Kn ratio of 0.1. Radicular apices were generated at IAA/Kn ratios of 1.0 or greater, but no shoot organogenesis was observed. These data suggest that A. americanum is more sensitive to auxins than cytokinins. Parasites of plants are known to secrete high levels of cytokinins, which stimulate the host to shuttle nutrients to the infected area, and so we suspect that A. americanum has reduced cytokinin sensitivity. Key words: Callus culture, Arceuthobium americanum, Explant, Response, Cytokinin, Insensitivity D.O.I. 10.3329/ptcb.v21i1.9557 Plant Tissue Cult. & Biotech. 21(1): 1-10, 2011 (June)